2023
DOI: 10.3390/molecules28073250
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and Synergistic Potential of Three Monoterpenoids against the Yellow Fever Mosquito, Aedes aegypti (Diptera: Culicidae), and the House Fly, Musca domestica (Diptera: Muscidae)

Abstract: As resistance to the limited number of insecticides available for medical and veterinary pests becomes more widespread, there is an urgent need for new insecticides and synergists on the market. To address this need, we conducted a study to assess the toxicity of three monoterpenoids—carvone, menthone, and fenchone—in comparison to permethrin and methomyl against adults of two common pests: the yellow fever mosquito (Aedes aegypti) and the house fly (Musca domestica). We also examined the potential for these m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Permethrin risk to adult butterflies and mosquitoes following ULV sprays was evaluated by comparing cumulative frequency distributions of measured exposures and available toxicity data. Toxicity data for five different mosquito species (Aa, Cq, Aedes albopictus , Anopheles gambiae and Anopheles quadrimaculatus ) include those reported in the literature (Pridgeon et al 2008 ; Chansang et al 2018 ; Estep et al 2018 ; Baker et al 2023 ) and determined in the present study. Toxicity data for adult butterflies ( Heliconius charitonia , Eumaeus atala , Junonia coenia , Vanessa cardui , Anartia jatrophae ) also include those reported in the literature (Salvato 2001 ; Hoang et al 2011 ).…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…Permethrin risk to adult butterflies and mosquitoes following ULV sprays was evaluated by comparing cumulative frequency distributions of measured exposures and available toxicity data. Toxicity data for five different mosquito species (Aa, Cq, Aedes albopictus , Anopheles gambiae and Anopheles quadrimaculatus ) include those reported in the literature (Pridgeon et al 2008 ; Chansang et al 2018 ; Estep et al 2018 ; Baker et al 2023 ) and determined in the present study. Toxicity data for adult butterflies ( Heliconius charitonia , Eumaeus atala , Junonia coenia , Vanessa cardui , Anartia jatrophae ) also include those reported in the literature (Salvato 2001 ; Hoang et al 2011 ).…”
Section: Methodsmentioning
confidence: 61%
“…A risk comparison for butterflies and mosquitoes requires data on toxicity and exposure for both insect groups. Several studies have reported 24-h LD50s for adult mosquitoes exposed to permethrin (Pridgeon et al 2008 , Agramonte et al 2017 , Chansang et al 2018 , Estep et al 2018 , Taylor-Wells et al 2018 , Tak et al 2020 and Baker et al 2023 ). The toxicity values reported in those studies ranged from 49 to 6960 ng/g for five different species ( Culex quinquefasciatus Say, Anopheles quadrimaculatus Say, Aedes aegypti Linnaeus, Anopheles gambiae Giles and Aedes albopictus Skuse).…”
mentioning
confidence: 99%
“…The synergistic effects of these compounds on other compounds have also been reported in various insects. 45,46 Notably, there was no positive correlation between the concentration of the compounds and their synergistic effect on the insecticides; instead, the synergistic effect of most of the compounds decreased with an increasing concentration. Among all of the EOs tested, wormseed oil had the best synergistic effect on βcypermethrin against B. germanica.…”
Section: ■ Discussionmentioning
confidence: 98%
“…The CAR21 susceptible strain of M. domestica (susceptibility confirmed by Baker et al [11]) and WHF strain of M. domestica used in this study were reared at the USDA-ARS Center for Medical, Agricultural, and Veterinary Entomology (CMAVE), using the protocols outlined in Geden et al [12]. The "wild" house flies (WHF) were originally collected from dairy farms in Florida, Minnesota, California, and Nebraska in 2014-2015.…”
Section: Rearingmentioning
confidence: 99%